Budgeting for a sustainable future Towards a roadmap of budgetary governance reform in Timor-Leste - Downes, Ronnie (OECD Publishing, 2018)
Despite being one of the newest countries in the world today, Timor-Leste has made great progress in building its institutions and economic capacity.With international support, Timor-Leste aims to improve its public financial management systems according to global benchmarks. Grounded upon the principles of the OECD's Recommendation on Budgetary Governance and building on existing diagnostic and analytical materials this review performs a fresh assessment of the country's current financial management systems and outlines a practical "roadmap" for progress in key areas of budgeting and planning over coming years